Collision dynamics of granular particles with adhesion - Brilliantov, Nikolai V.; Albers, Nicole; Spahn, Frank; Pöschel, Thorsten (Physical Review E, 2007)
We investigate the collision of adhesive viscoelastic spheres in quasistatic approximation where the adhesive interaction is described by the Johnson, Kendall, and Roberts (JKR) theory. The collision dynamics, based on the dynamic contact force, describes both restitutive collisions quantified by the coefficient of restitution ε as well as aggregative collisions, characterized by the critical aggregative impact velocity gcr. Both quantities ε and gcr depend sensitively on the impact velocity and particle size. Our results agree well with laboratory experiments. © 2007 The American Physical Society.